The Agency of Journalists in Competitive Authoritarian Regimes: The Case of Ukraine During Yanukovich’s Presidency - Somfalvy, Esther (2021)
On the example of Ukraine during the Yanukovich presidency (2010–2014) this article explores which factors support journalists’ agency in relation to censorship pressure in a competitive authoritarian regime. It shows that a critical mass of journalists existed who reacted to censorship pressure with rejection. Based, first of all, on 31 semi-structured interviews, we examine the working conditions of prominent national journalists and analyse how they describe their role and motivations. We argue that the nature of competitive authoritarianism offers journalists opportunities for critical reporting, but that it is individual characteristics of journalists—including professional ethics, networks, and job mobility—which define whether and how the respective opportunities are used.